(untitled) (Journal of the College of Languages (JCL), 2018)
Harold Pinter often portrays the dilemma of obliterated figures that are incapable of feeling of their own existences. These figures feel exhausted and frustrated in a world that deprives them their humanity. They retreat into a limited world where they look for security and protection. The characters’ feeling of security is threatened by outside forces represented by intruding persons who stand for the mysterious powers that are indefinable. The conflict between these intruders and the characters finally ends with the characters’ defeat. The reason for the intruders’ attack on the victims remains ambiguous and is not explained. The element of mystery pervades Pinter’s plays and represents one of its main characteristics. This paper attempts to investigate how Pinter treats this dilemma in his first play The Birthday Party (1957). How man does escape from his reality, what kinds of danger attack man, why man cannot fight against these threats, are the questions which this paper is trying to answer.